Exploring environmental efficiency of the European agricultural sector in the use of mineral fertilizers. - Expósito-García, Alfonso; Velasco, Francisco (Elsevier, 2020)
This study analyzes the environmental efficiency of the agricultural sector regarding the use of mineral fertilizers in the period 2001e2012 for a group of European countries. Specifically, efficiency is assessed through a dynamic Data Envelopment Analysis methodology. This method aims to analyze temporal efficiency changes through the estimation of Malmquist indexes with increasing and decreasing temporal windows. Findings show that most countries register efficiency advances in the periods 2002 e2003 and 2007e2008. Specific countries, such as Belgium-Luxembourg, Denmark, Netherlands, Sweden and United Kingdom, register persistently higher values of the estimated Malmquist indexes. This study contributes to the existing literature by assessing country-specific efficiency paths, as well as by identifying best-performing countries from which lessons can be learnt. A brief review of main measures taken by a selected group of benchmark countries is offered.
https://openpolicyfinder.jisc.ac.uk/id/publication/13808
Keywords: Fertilizantes; Agricultura - Aspectos ambientales; Environmental efficiency; Agriculture; Mineral fertilizers; Data Envelopment Analysis